Management of Plant-Parasitic Nematodes in Florida Cotton Production - Zane Grabau (EDIS)
This 8-page fact sheet written by Zane J. Grabau and published in January 2017 by the UF Department of Entomology and Nematology explains how to diagnose and manage nematode problems in cotton production.http://edis.ifas.ufl.edu/ng015